Nowy wymiar stosunków rosyjsko-irańskich. Wpływ porozumienia na regionalną równowagę sił - Dworska, Żaklina (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The present analysis is concerned with an examination of the impact of the Comprehensive Strategic Partnership Agreement between the Islamic Republic of Iran and the Russian Federation, dated 17 January 2025, on the regional balance of power. Existing scholarly works predominantly focus on the analysis of bilateral relations characterised by opposition to Western hegemony, a perspective reflected in earlier treaties and cooperative initiatives between Iran and Russia.
Keywords: Iran; Rosja; porozumienie strategiczne; geopolityka; sankcje międzynarodowe; Russia; strategic partnership; geopolitics; international sanctions